Analisis Perancangan PC (Personal Computer) Router Proxy Untuk Menggabungkan Tiga Jalur Koneksi Di Indospeed - Bangun Harizal; Adnan Purwanto; Wahyu Pamungkas (JURNAL INFOTEL, 2012)
Router very important for computer network. To get the router can buy a router products but can also design your own using personal computers. Mikrotik is one of the router manufacturer that provides products in the form of hardware or software. If you want to pay less to design a router can use operating system Ubuntu. This operating system is open source and provided free of charge by the manufacturer. If you want to design a router with this OS can make use of personal computers are often used in homes or offices. Merging the performance of both types of routers can also be usedto cover the lack of one another. With the proxy on a local network then the use of bandwidth can be saved. Becausethere are several websites cached and stored therein if the same website is accessed by other users, the router transmits only from the proxy to the computerwhich make the request.